Venomics of the scorpion Tityus ocelote (Scorpiones, Buthidae): Understanding venom evolution in the subgenus Archaeotityus - Díaz Oreiro, Cecilia (2022)
The subgenus Tityus (Archaeotityus) includes small variegated species considered until recently, a basal group within Tityus, one of the most diverse and medically relevant genera of scorpions in the New World. Archaeotityus species are distributed in the humid forests of Lower Central America and the Choco, Guiana Shield, and Amazonian regions. Due to their size and habits, Archaeotityus species are not usually considered dangerous, however, there are some clinical reports that show otherwise. To contribute to the toxinological knowledge of these poorly explored species, we characterized the venom of Tityus ocelote from three localities in Costa Rica. In addition, we assessed the evolutionary relationships of putative sodium channel-modulating peptides found in this species with those reported for other members of the genus, through a maximum likelihood phylogenetic analysis based on their amino acid sequences. We observed the presence of homologs of previously identified NaTx from the species Tityus (Archaeotityus) clathratus and some other putative Na+ and K+ channel modulating peptides related to the T. bahiensis group. In addition, we sequenced some peptides related to toxins present in the venom of the subgenus Atreus, such as those reported for T. obscurus, T. pachyurus, and the Costa Rican endemic species T. dedoslargos. Our phylogenetic analysis suggests that the venom of this Archaeotityus species is very complex and that some of the ion channel toxins expressed in it are related to distinct lineages within the genus Tityus, which could represent a plesiomorphic condition conserved in this group of scorpions of the New World.